2012
DOI: 10.1001/archgenpsychiatry.2011.1858
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Factors With Apathy in Community-Dwelling Elderly Individuals

Abstract: Symptoms indicative of apathy are common in community-dwelling nondemented older people who are free from depression. The independent association of stroke, other cardiovascular disease, and cardiovascular risk factors with symptoms of apathy suggests a causal role of vascular factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(144 citation statements)
references
References 31 publications
15
125
4
Order By: Relevance
“…Logistic analysis was performed to evaluate the association between CFPWV and a dichotomous measure of depressive symptoms. It has been suggested 24 that cerebral small vessel disease may be associated with, in particular, apathy-related or motivation-related symptoms of depression, but not with mood-related symptoms. Therefore, we performed logistic regression analyses to evaluate the association between CFPWV and individual apathy items of the GDS-15 score as the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic analysis was performed to evaluate the association between CFPWV and a dichotomous measure of depressive symptoms. It has been suggested 24 that cerebral small vessel disease may be associated with, in particular, apathy-related or motivation-related symptoms of depression, but not with mood-related symptoms. Therefore, we performed logistic regression analyses to evaluate the association between CFPWV and individual apathy items of the GDS-15 score as the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…"; and 3) "Do you feel full of energy?". 24,25 As described previously, 24,25 we distinguished an apathy subscale that included all apathy items (range 0-3; GDS-3A). Presence of apathy was defined as a GDS-3A score of 2 or 3 versus no apathy (score of 0 or 1).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Furthermore, apathy was associated with cognitive and functional impairments in elders adjudged to have normal cognition [48]. It has been reported that up to a quarter of nondemented community-dwelling elderly individuals have apathy (most without concomitant depression) [50,51]. In this population a past history of stroke (OR 1.8; 95% CI 1.4–2.3) [50] or other vascular diseases are risk factors for apathy [51].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers of comparable age, apathy was found in 6.0% and 53 In another study, a community-based sample of elderly, a prevalence of 19.9% was found. 54 This suggests that not all cases of poststroke apathy are directly attributable to the stroke, although its prevalence is higher in patients with a history of multiple strokes.…”
Section: Prevalencementioning
confidence: 99%